Frequency of Domestic Violence in Psychiatric Patients and Related Factors - Korkmaz, Sevda; Korucu, Tuba; Yildiz, Sevler; Kaya, Suheda; Izci, Filiz; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Objective: Objective of the present study is to determine prevalence of domestic violence among married female patients who have applied to our psychiatry outpatient clinic, and to investigate the relationship between exposure to violence and levels of anxiety and depression. Method: One hundred consecutive married female patients were included into the study. Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and a sociodemographic and clinical data form designed by the authors were applied to each case. Furthermore, all participants were asked to complete a questionnaire including questions such as whether there was violence (economic, physical, sexual and psychological) at home; if present, what its frequency and duration is; and whether the partners were subject to violence during their childhood. Results: It was determined that 76% of the patients were subjected to at least one type of violence during marriage, 68% were exposed to verbal, 45% were exposed to physical, 39% were exposed to economic, and 11% were subject to sexual violence. As level of education was increased, the rate of being a victim of physical violence was increased directly. Of females who were the victims of physical violence (n=18), 40% reported that they inflicted violence to their children, and 15 of these patients (33%) said that they attempted a suicide during their marriage. Conclusion: In the present study, it is determined that domestic violence is correlated with increases in anxiety and depression scores. Independently from violence type, it is determined that domestic violence causes increased number of suicide attempts.
Keywords: Anxiety; depression; domestic violence